Striking an Appropriate Balance Among Public Investment, Growth, and Debt Sustainability in Cape Verde - Mu, Yibin (IMF Working Papers; Working Paper, 2012)
Despite relatively fast economic growth over the past few years, Cape Verde's public debt to GDP ratio has risenrapidly. Achieving an appropriate balance among public investment, growth, and debt sustainability has become a priority for the Cape Verdean authorities. The IMF-World Bank debt sustainability analysis (DSA) framework has helped the authorities monitor the risks of debt stress. However, the DSA has a number of limitations. This paper intends to complement the DSA by addressing aspects currently not covered by the DSA. The paper evaluates public investment scaling-up strategies in Cape Verde by customizing the Buffie and others (2012) model for Cape Verde and conducting various scenario and sensitivity analysis. The paper assesses Cape Verde's public debt risks, taking into account the link between public investment and growth. The paper concludes that the size of scaling-up and aspects of the economic structure have significant impact on the outcome of the public investment. A very large surge in public investment may lead to a debt to GDP ratio that reaches dangerous levels based on the usual DSA criteria. A more moderate scaling-up of public investment may contribute better to stable and sustained growth over the medium and long run. In addition, it is critical that the authorities ensure the quality of public investment.